2004
DOI: 10.1111/j.0022-202x.2004.22418.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neuropeptide Galanin and Galanin Receptors in Human Skin

Abstract: These studies were supported by a Grant of the Austrian Science Foundation (P14906), the Vereinigung zur Fö rderung Pä diatrischer Forschung und Fortbildung Salzburg, and the Medizinische Forschungsgesellschaft Salzburg. We thank Peter Petzelbauer (Department of Dermatology, University of Vienna) for providing samples of cultured human dermal microvascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Previous studies reported galanin-like immunoreactivity (Gal-LI) in nerve terminals and fibres in the dermis and basal layers of the epidermis as well as in nerves surrounding sweat glands (4)(5)(6). In addition, Gal-LI was found in keratinocytes and ductal cells of eccrine sweat glands (5).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies reported galanin-like immunoreactivity (Gal-LI) in nerve terminals and fibres in the dermis and basal layers of the epidermis as well as in nerves surrounding sweat glands (4)(5)(6). In addition, Gal-LI was found in keratinocytes and ductal cells of eccrine sweat glands (5).…”
Section: Introductionmentioning
confidence: 97%
“…The main source of collagen is believed to emanate from fibroblasts and myofibroblasts surrounding the wound site (1). Previous findings suggest that macrophages may affect fibroblast recruitment to the wound site and collagen deposition (2)(3)(4)(5). In vitro, macrophages have been classified as M1 inflammatory macrophages or M2 tissue repair and pro-angiogenic macrophages (6).…”
Section: Introductionmentioning
confidence: 99%
“…Murine and human skin specimens were stained by using affinity-purified anti-alarin antisera. Because the homology between the human and the murine peptide is only 60%, two antisera, one directed against the murine alarin peptide (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and one directed against the human homologue, were used. Alarin-like immunoreactivity (alarin-LI) was detected in pericytes covering microvascular arterioles and venules on their abluminal surfaces in the murine as well as in the human dermis, whereas in larger vessels alarin-LI was detected in layers of smooth muscle cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma extravasation was used as an index of inflammatory edema formation and measured as previously described (49). Briefly, test agents [SP, CGRP, galanin, GALP (1-60), GALP (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), alarin , and alarin (3-25)] were diluted in Tyrode's solution and stored on ice. 125 I-BSA (45 kBq in 100 l of saline) was administered i.v.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation